The Influence of the Principal's Leadership and Work Culture on Teacher Performance at SDN Lima Puluh Pekanbaru - Desilawati, Desilawati; Suanto, Elfis; Aibonotika, Arza (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
Teacher performance is required to be examined in depth. The factors that lead to the problems are related to teacher performance. Hence, this paper examines the in-depth influence of the principal's leadership and work culture on teacher performance at SDN Limapuluh Pekanbaru. This research uses a quantitative descriptive approach. Data collection techniques use observation, documentation, and questionnaires. The research subjects involved 142 teachers at SDN Limapuluh Pekanbaru. The sample of the research was carried out using Proportional Random Sampling, namely a method of taking samples from members of the population using a random method without paying attention to the strata in the population. The research results indicate that 1) the principal's leadership has a significant positive influence on teacher performance with a significance value of 0.000 or less than an alpha value of 0.05, 2) work culture has a significant positive influence on teacher performance with a significance value of 0.000, and 3) the principal's leadership and work culture jointly influence teacher performance with a significance value of 0.000 and an R-Square value of 0.758. This indicates that the proportion of influence of the principal's leadership and work culture variables on the teacher performance variable is 75.8%.